National Workshop on Asthma and the Environment - Tom Wood; Pierre Ernst (Canadian Respiratory Journal)
A national workshop on asthma and the environment was held October 23 and 24, 1992. in Montreal, Quebec. Twenty-nine speakers presented data on asthma from a Canadian perspective. A nun1hcr of recommendations were produced which will influence future asthma research and management in Canada.